Pengembangan Produk Snack Bar sebagai Makanan Selingan Sumber Kalium dan Antosianin untuk Hipertensi - Fahira Diva Kirani; Gurid Pramintarto Eko Mulyo; Raden Roro Nur Fauziyah; Nitta Isdiany (Jurnal Gizi dan Dietetik, 2025)
High blood pressure or hypertension is one of the main risk factors for cardiovascular disease. Hypertension can be prevented and treated through non-pharmacological interventions with the DASH diet. One of the principles of the DASH diet is to consume foods high in potassium and bioactive compounds, namely anthocyanins. This study aims to develop a functional snack bar product made from red bean flour as a source of potassium and purple sweet potato flour as a source of anthocyanins, and to evaluate its chemical, sensory, and acceptance characteristics in hypertensive patients. The study used three formulations, F1: 105 g red bean flour : 45 g purple sweet potato flour; F2: 90 g : 60 g; F3: 75 g : 75 g. The analyses conducted included proximate tests (moisture, ash, fat, protein, carbohydrate content), functional content tests (potassium and anthocyanin), and organoleptic tests by semi-trained panelists and hypertensive patients using a hedonic scale. The organoleptic test results showed that there were no significant differences in color, aroma, texture, taste, or overall appearance. Formula 3 was the most preferred formula by the panelists. The proximate test results showed an energy content of 266.3 kcal, protein 5 g, fat 8.7 g, carbohydrates 42 g, potassium content 461.3 mg, and anthocyanin 0.3 mg per serving. Based on these results, the modified snack bar has the potential to be a high-potassium functional food and a source of anthocyanin for hypertensive patients.